Influência do gerenciamento de resultados por decisões operacionais na remuneração executiva - Fontana, Danieli Ferreira Flôres (2023)
The study aimed to analyze the influence of earnings management through operational decisions on executive management. Through descriptive research, with a quantitative approach, carried out through documentary analysis of secondary data from 90 non-financial publicly traded companies involved in B3, from 2015 to 2021. The GRDO's influence on operational negotiations occurred through the analysis of two forms of earnings management through operational decisions, corresponding to the abnormal value of operating cash flow and the abnormal value of the production level. Also investigating the effects of these practices on the portion of payments that are misaligned with the executive's financial performance and market. The results demonstrated that GRDO practices positively and directly influence the salaries of CEOs and statutory directors. Further pointing out that the remunerations of CEOs and other directors are linked to different performance indicators, where CEOs have their remunerations aligned with market performance, while statutory directors present contributions aligned with financial performance, however, the results also draw attention to the existence of a significant portion of agents' contributions that is explained by variables other than performance, with GRDO being one of the elements capable of explaining executive remuneration. The research contributes to explaining part of the determinants of executive employees, with emphasis on CEOs, who use operations management practices to modify the result and, as a consequence, increase the level of income.